Developing language awareness for preschoolers and lower secondary students with dice games (Training and Practice : Journal of Educational Sciences, 2021)
An adequate level of language awareness is indispensable for literacy learning and further language development. Many young children do not have an adequate level of language awareness when entering school. Both national and international research results urge that we start preparing literacy skills in kindergarten. In addition to general language experience, a conscious focus on language elements also plays a role in this. In this study, we briefly detail the levels of language awareness, and then publish some types of dice games that help children engage in language in a playful, enjoyable way.